G43(P) Difficulties in complying with the bspghan guidelines for diagnosis and management of celiac disease (2013). (12th March 2018) - Mitchell, C; Thakur, A; Onyeador, N; Bilal, I
Abstract : Aims: To audit our paediatric department's practice of diagnosis and management of celiac disease, comparing it to the BSPGHAN and Coeliac UK guidance published in 2013, to review and consider improvements to our current practice. Method: Collection of data from 2015–2017 including all patients aged <18 years old with a positive tissue transglutaminase (tTG). Electronic records were used to gather information regarding other serological tests (endomysial antibodies (EMA)), genetic tests (HLA DQ2/DQ8), and biopsy results; as well as time-to-follow up with both the dietician and clinician. Results: Of the 55 children with a positive tTG there were sufficient data to include 40. 10/40 were asymptomatic; 30/40 symptomatic, and the ratio of females to males was 3.4:1. This audit demonstrated that 67.5% were diagnosed according to the national guidelines, and for those cases where the guidance was not adhered to it was most commonly because a biopsy had not been performed (see table 1 below). Only 17% of patients were seen by the dietician within 2 weeks following diagnosis, and only 40% within 6 months. 77% were seen by a clinician at 12 months but only 47% had a repeat tTG at this appointment. Finally, only 20% of those eligible were transitioned to adult services. Conclusion: Clinicians face many difficulties when diagnosing celiac disease. Most notably convincing families to return to a gluten-containing diet prior to further investigations; and encouraging families to consider a biopsy in asymptomatic patients. However, there are many occasions when serological tests have been omitted by clinicians, probably due to a lack of awareness. Improvements are needed to reduce the length of time from diagnosis to dietician follow up, and follow up at 12 months needs to include repeat tTG assessment. Finally, increased awareness is needed on the national policy to transition celiac patients to adult secondary care.